Vibration phase difference analysis of long-span suspension bridge during flutter. (1st February 2023) - Wu, Lianhuo; Woody Ju, J.; Zhang, Jinxiang; Zhang, Mingjin; Li, Yongle
Highlights: The mechanism of the bimodal coupling phase difference varying along the span is revealed. The phase difference of vibration increases from the mid-span to the bridge tower. The vibration track of the main girder and main cable are elliptical and asynchronous along the span. Abstract: The research on vibration characteristics of long-span bridges is of great importance to flutter analysis, yet the literature is limited which concerns the phase difference characteristic of the full bridge. This study thus aims to investigate the vibration phase difference characteristics and mechanism along the main span during flutter. The time-domain flutter analysis was conducted in a long-span suspension bridge. The results manifest that the vibration in different directions at the same position and the vibration in the same direction at different positions of the main girder and the main cable all exist phase difference, which varies along the main span. The deduced phase difference equation reveals that the variable of the distance from mid-span is in cosine term of the denominator, making the increasing of the distance resulting in the growth of phase difference. Due to the variation of phase difference, the vibration of the main girder and main cable along the span is asynchronous. The motion trajectories of individual points are elliptic and vary along the main span. These findings can help understand the flutter performance and mechanism of long-span bridges.